A real-time estimation approach of the electric power harmonics by measuring discrete spectrum energy center of symmetric windows. Issue 3 (3rd May 2016) - Tang, Yi; Li, Xue; Fang, Yongli; Liu, Hao
Abstract : Purpose: – Significant amount of harmonics and inter-harmonics are being injected into the power system because of the increasing use of power electronics and large non-linear loads. Therefore, the purpose of this paper is to analyze their contents in real time. Design/methodology/approach: – The frequency and phase of an electric power harmonic or inter-harmonic can be estimated by using the discrete spectrum energy center of symmetric windows, the amplitude calculation of an electric power harmonic or inter-harmonic can be calculated by using the Pasival theorem, and their relative estimation error is only decided by the distribution of windows' energy in the frequency domain, which equals the proportion of the spectrum energy occupied in the side lobe to the whole. Findings: – The results of the digital simulation and experimental tests show that the method proposed in this paper has the same measurement precision as and more advantages in computational complexity and burden over other methods, which are based on multipoint interpolation or interpolation polynomial windowed. Originality/value: – The method is very suitable to be used to real-time measurement in a single chip DSP micro-processor.